Oxidative stress and genotoxicity in the South American Cichlid, Australoheros facetus, after short-term sublethal exposure to endosulfan - Crupkin, Andrea Carina (2013)
Short-term responses at the antioxidant enzymatic systems, together with genotoxic effects were studied in the freshwater ﬁsh Australoheros facetus, exposed to endosulfan (ES) (0.02, 0.5, 5, 10 lg/L) for 24 h. Brain was the most responsive organ, showing inhibition of the enzymatic systems together with an increase of hydrogen peroxide (H2O2) content. Concentration-dependent inhibition was observed for superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR) with IC25 values of 0.012, 0.017, 0.018 lg/L, respectively. In liver, a similar behavior was observed for SOD with IC25 values of 2.22 lg/L. In addition, increased thiobarbituric acid reactive substances (TBARs) at 5 lg/L and H2O2 at 5 and 10 lg/L were observed. No effects were evidenced on ethoxyresoruﬁn O-deethylase (EROD), glutathione-S-transferase (GST), GR and CAT activities. In gills, only H2O2 decreased at 0.5 and 5 lg/L ES. Genotoxic effects were detected by the increase of the frequency of both, nuclear abnormalities (NA) at 0.02 lg/L and micronucleus (MN) at 5 lg/L. Environmentally realistic concentrations of ES exerted toxic responses in A. facetus, encouraging the further ﬁeld validation of the observed pattern (tissue speciﬁcity, sensitiveness and concentration-response relationship) as a potential suit of biomarkers for assessing acute sublethal effects in A. facetus under short-term pulsed exposure to ES.